Care of newborns with congenital diaphragmatic hernia (Archives of Pediatrics of Uruguay, 2023)
Congenital diaphragmatic hernia is a defect in the diaphragm that leads to herniation of theabdominal contents of the thoracic cavity during the intrauterine period.Morbidity and mortality are determined by the association with other malformations, the degree ofpulmonary hypoplasia and the presence of secondary pulmonary hypertension.It has an estimated incidence of 1 every 2,500-3,000 live newborns, and in 60% of the cases it is an isolated malformation.It is an evolutionary pathology that can be diagnosed from week 20-24; it is most commonly located in the left posterolateral.It is a pathology that requires intensive care at birth and after delivery and once the patient has been stabilized, surgical action is required.The objectives of this work are to understand the general characteristics of the pathology in order to refine its manipulation and achieve optimal counseling for parents at the newborn’s prenatal and postnatal stages.
Keywords: Congenital diaphragmatic hernias; Newborn